BERGADA RAJAMALA SEMANGGI - Mulyadi, Tubagus; Slamet, Slamet (Institut Seni Indoensia Surakarta, 2019)
ABSTRACTRajamala is a puppet character from Mahabarata story which represents an incarnation of Dewi Loroamis’ disease in a form of a small-giant little boy. Rajamala is a symbol of disaster that must be removed from human life. This event inspired Sultan HB X to create a ship Cantik Baito in the form of Rajamala’s face in order to get safety trip to Madura through Semanggianchorage at Bengawan Solo River. The Rajamala at Cantik Baito, then, became inspiration for the Semanggi community to create“Bergada Rajamala”, an army with Rajamala mask. This creation is related to the anchoragesite in Semanggi. The problem of this study is about how to brand Rajamala as an icon of Semanggi and why it is necessary to make “Bergada Rajamala” in Semanggi parade. This study uses the method of creation through observation, exploration, experimentation, reflection, and formation. The results obtained include the creation of the parade dance or “Bergada” dance that use Rajamala mask costumes that is called “BergadaRajamalaSemanggi.”KeyWords: Rajamala, Bergada, Semanggi.